BS EN IEC 61558-2-5. Safety of transformers, reactors, power supply units and combinations thereof. Part 2-5. Particular requirements and test for transformer for shavers, power supply units for shavers and shaver supply units (28th February 2023) - British Standards Institution,
No abstract available